The impact of life events on job satisfaction - Georgellis, Yannis; Lange, Thomas; Tabvuma, Vurain (Academic Press, 2012)
Employing fixed effects regression techniques on longitudinal data,we investigate howlife eventsaffect employees' job satisfaction. Unlike previous work–life research, exploring mostly contemporaneouscorrelations, we look for evidence of adaptation in the years following major lifeevents. We find evidence of adaptation following the first marriage event, but we find that thebirth of the first child has a long-lasting impact on employees' job satisfaction. Our findings alsosuggest that there is a general boost in job satisfaction prior to first marriage and to a lesser extentprior to the birth of the first child, consistentwith evidence of anticipation. Accordingly, our studyprovides some of the first evidence on the dynamic effect of non-work related factors on jobsatisfaction and it introduces a novel methodology and a new perspective for investigating thedynamic interaction between the work and life domains.